MATEC Web of Conferences - Vasilevsky; Razva Specialist in the field of thermal engineering Senior Lecturer of Tomsk Polytechnic University, Candidate of technical sciences; Zaharov; Shabirov (EDP Sciences, 2018)
The phenomena at interaction of agglomerate of disperse material with the surface of the inertial device are considered. It is revealed that tension in the interactions between the agglomerate surface can reach values comparable to atmospheric pressure, which is the reason for the formation of solid deposits, what is the reason of formation of strong deposits which, in turn, are defined by the autohesion communications of particles forming agglomerate.